Adequacy of Some Locally Produced Complementary Foods Marketed in Benin, Burkina Faso, Ghana, and Senegal - Dimaria, Sara Antonio (Nutrients, 2018)
Adequate complementary foods are needed to help reduce the high prevalence of stunting in children in many Low and Middle Income Countries (LMICs). We assessed the availability, affordability, and nutrient adequacy of imported and locally produced processed cereal-based blends (PCBBs), marketed as complementary food for young children in Benin, Burkina Faso, Ghana, and Senegal. In total, 19 local producers and 275 points of sale in the four countries were surveyed to evaluate the quantities and accessibility of PCBBs. In addition, 32 PCBBs were analysed for their nutritional composition and packaging information. The results showed that only 7 out of 32 PCBBs could be classified as nutritionally satisfactory. Access to the products was insufficient in all surveyed settings. At the points of sale, the PCBB market was dominated by imported products, even though two out of four imported PCBBs were not nutritionally satisfactory. Imported PCBBs were two to three times more expensive than locally produced PCBBs. Labelling of the PCBBs was inadequate in many aspects. Technical support should be offered to local PCBB producers to ensure the adequate formulation and supply of an appropriate vitamin and mineral premix. The development of national specific regulations on PCBB composition and labelling is strongly recommended in these countries.